KOLABORASI ORGANISASI MASYARAKAT DENGAN SEKOLAH MENENGAH PERTAMA UNTUK MENCAPAI TUJUAN PEMBELAJARAN IPA - Arista Eka Kumalasari; Akhmad Alifurizal Romli; Dina Emiliana; Niken Putri Arina; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (FKIP e-PROCEEDING, 2022)
This study aims to find out how important the collaboration of organizations in the community is with the process of ongoing science learning activities in Junior High Schools. This research was conducted in October 2022 using this type of research in the form of basic and supporting data from books and other journals. Collaborative learning makes it easier for students to learn and work together, contribute thoughts to each other and be responsible for the achievement of learning outcomes in groups and individuals. The variables observed are in the form of the causes of collaboration, progress in science and technology, collaboration between educational institutions, teachers/teachers and practitioners who have special skills, as well as the government and the business world.With collaborative learning, various benefits are known for educators and students themselves. The results showed that collaborative learning can improve students' skills in working together and can improve the achievement of student learning outcomes through the learning process.